HEALTH PROFILE OF INDUSTRIAL FEMALE WORKERS AND THEIR REPRODUCTIVE HEALTH RISK IN BEKASI DISTRICT, INDONESIA - Narila Mutia Nasir; Febrianti Febrianti; Iting Shofwati; Raihana Nadra Alkaff; Dela Aristi (IAKMI South Tangerang Branch, 2022)
Abstract Background: Maternal and child morbidity and mortality remains problems in Indonesia. Based on the life cycle approach, the improvement should be done before the pregnancy which targeted to reproductive age women. One group that need attention is industrial female workers. It is crucial to know their health profile and reproductive health risk they may have. Objective: to describe the health profile of industrial female workers and their reproductive health risk in Bekasi District, Indonesia Method: We used cross sectional study design and involved 386 industrial female workers who live in Bekasi Disrict as respondents. The data collection was carried out during November 2021. We interviewed the respondents using questionnaire and measured their body mass index, total body fat, visceral fat, blood pressure, and random blood sugar. We analysed the data using univariate analysis. Result:. The respondent who categorized as obese based on body mass index (52.8%), total body fat (72%), visceral fat (9.8%). 11.9% respondents were suspected to hypertension, while 26.9% were suspected to hypertension according to diastole blood pressure measurement. The distribution of respondents who had potential risk to get diabetes was 2.3%. The anemia status of respondents was 10.4%. The result analysis shows that 88.3 % of respondents had risk to experience during pregnancy, delivery, and risk to have stunted baby because their health profile. Conclusion: The health profile of industrial female workers in this study indicated they have risk to obesity, diabetes mellitus and hypertension. This health profile placed them to the reproductive health risk, especially related to pregnancy and delivery. They also have risk to have stunted baby if they experience pregnancy. Keywords:, Female workers, industrial, health profile, reproductive health risk, Indonesia